PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK PESERTA DIDIK - Supriyadi; Ahmad Asrori; Yuli Habibatul Imamah (UNISAN JURNAL, 2023)
This study aims to analyze and describe the role of PAI teachers in fostering the morals of students at the Rabbani Muara Enim Integrated Islamic Elementary School. This research is a qualitative research, because the approach is based on qualitative evidence. Data collection techniques used in this research are observation, interviews, and documentation studies. While data analysis consists of three steps, namely data reduction, data display, and drawing conclusions. The role of the PAI teacher as an educator and teacher is not optimal, due to the lack of volume of meetings between the PAI teacher and students, the lack of effort by the PAI teacher to monitor student development through portfolio assessment, the lack of intensive efforts to instill moral values ​​in students, the lack of mastery of material learning, did not arrange the learning program properly, did not implement the learning program optimally, did not evaluate the results and learning process optimally